2021
DOI: 10.1186/s12872-021-02263-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between anion gap and mortality of aortic aneurysm in intensive care unit after open surgery

Abstract: Background There has not been a well-accepted prognostic model to predict the mortality of aortic aneurysm patients in intensive care unit after open surgery repair. Otherwise, our previous study found that anion gap was a prognosis factor for aortic aneurysm patients. Therefore, we wanted to investigate the relationship between anion gap and mortality of aortic aneurysm patients in intensive care unit after open surgery repair. Methods From Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Furthermore, Masevicius et al [ 1 ] conducted a prospective cohort study and discovered that increased unmeasured anions (calculated as AG − lactate) was positively correlated with the risk of mortality in 4901 medical and surgical ICU patients (OR, 1.04; 95% CI, 1.02-1.06). Several recent retrospective studies also demonstrated that elevated AG within the first day of ICU admission was related with increased mortality among critically ill patients with sepsis [ 8 ], congestive heart failure [ 10 ], aortic aneurysm [ 7 ], cardiogenic shock [ 23 ], and acute pancreatitis [ 24 ]. The different study designs and the heterogeneity of study populations may underlie the conflicts in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Masevicius et al [ 1 ] conducted a prospective cohort study and discovered that increased unmeasured anions (calculated as AG − lactate) was positively correlated with the risk of mortality in 4901 medical and surgical ICU patients (OR, 1.04; 95% CI, 1.02-1.06). Several recent retrospective studies also demonstrated that elevated AG within the first day of ICU admission was related with increased mortality among critically ill patients with sepsis [ 8 ], congestive heart failure [ 10 ], aortic aneurysm [ 7 ], cardiogenic shock [ 23 ], and acute pancreatitis [ 24 ]. The different study designs and the heterogeneity of study populations may underlie the conflicts in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing 19 documented studies, a meta-analysis stated that AG was not recommended to evaluate the risk for mortality in critically ill patients [ 6 ]. Whereas, recent studies demonstrated that increased AG was associated with high mortality in ICU patients with aortic aneurysm [ 7 ], sepsis [ 8 ], disseminated intravascular coagulation [ 9 ], and congestive heart failure [ 10 ]. Besides, a study conducted in COVID-19 patients showed that AG was one of the most decisive features for mortality prediction in a machine learning model [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 18 ] studied the association between the AG and mortality in critically ill patients with cardiogenic shock (CS) and suggested that higher AG was related to increased risk of 30-day, 90-day, and 1-year all-cause mortality, HRs (95% CIs) were as follows: 1.62 (1.14–2.30), 1.35 (1.04-1.84), and 1.38 (1.03-1.84), respectively. Gao et al [ 24 ] found that the mortality of aortic aneurysm (AA) in ICU after open surgery increased with increased AG level (OR 1.286, 95% CI: 1.053-1.651) and the growing tendency of mortality was sharper when the AG level was higher than 12 mEq/L. Additionally, Cheng et al [ 16 ] proposed higher AG as a significant predictor of 30-day, 90-day, and 365-day all-cause mortality compared with lower AG (HR, 95% CI: 1.54, 1.33–1.75), 1.55 (1.38-1.73), and 1.46 (1.31-1.60) in critically ill patients with acute kidney injury (AKI).…”
Section: Discussionmentioning
confidence: 99%
“…Patients were grouped into quintiles by the AG according to cutoffs derived from clinical experience and literatures [ 16 , 18 , 23 , 24 ]. The Kaplan-Meier curves were presented for survival analysis, and log-rank tests were used to compare survival rates between groups.…”
Section: Methodsmentioning
confidence: 99%
“…The serum anion gap (AG) arises when there is an excessive synthesis of organic acid anions and/or an equivalent reduction in anion secretion [ 4 , 5 ]. AG is a potential parameter that can be computed mathematically and utilized in diagnosing different metabolic acidosis [ 6 , 7 ]. The numerous studies conducted recently have revealed that anion gap (AG) has a promising predictive value for various ailments, for instance, heart failure [ 8 ], coronary heart disease [ 9 ], and myocardial infarction [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%